POLITICAL MARKETING STURMAN PANJAITAN PADA PEMILIHAN UMUM LEGISLATIF TAHUN 2024 DI KOTA BATAM - Sibarani, Arauna Elkana; Nisaa, Fadhiilatun (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
he 2024 Legislative Elections show a growing trend in the use of political marketing strategies by legislative candidates. One interesting figure to analyze is Sturman Panjaitan, an incumbent legislative candidate from Batam City. Sturman not only relies on the strength of his formal political network but is also able to